2007
DOI: 10.2105/ajph.2005.071167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Posttraumatic Stress Disorder in a Coastal Fishing Village in Tamil Nadu, India, After the December 2004 Tsunami

Abstract: Two months after the December 2004 tsunami in Tamil Nadu, India, we surveyed adults aged 18 years or older in a severely affected coastal village using structured interviews and the Harvard Trauma Questionnaire. The prevalence of posttraumatic stress disorder was 12.7% (95% confidence interval [CI]=9.4%, 17.1%), and odds of posttraumatic stress disorder were higher among individuals with no household incomes, women, and those injured during the tsunami. In addition to promoting feelings of safety, intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 11 publications
6
64
0
2
Order By: Relevance
“…18 A study based on data from one village in India reported a similar finding. 19 Demographic characteristics and standard measures of socioeconomic status were not statistically significant predictors of PTSD in the study of Thailand. In India, however, the odds of PTSD were higher for women and those injured by the tsunami.…”
Section: Comparisons To Evidence From Other Settingsmentioning
confidence: 75%
“…18 A study based on data from one village in India reported a similar finding. 19 Demographic characteristics and standard measures of socioeconomic status were not statistically significant predictors of PTSD in the study of Thailand. In India, however, the odds of PTSD were higher for women and those injured by the tsunami.…”
Section: Comparisons To Evidence From Other Settingsmentioning
confidence: 75%
“…Earlier disaster researchers have examined a variety of situations, including the collapse of dams with resultant flooding, [7] hurricanes, [5,8] tsunamis, [9,10] the 2001 World Trade Centre attacks, [11] and the Oklahoma City bombing. [12] Other studies have documented the effects of earthquakes, mainly in America and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Investigadores que estudiaron trastornos mentales relacionados al tsunami del sudeste asiático, en donde la prevalencia de trastornos de estrés postraumático fue mayor a la observada en los habitantes chilenos, concuerdan con identificar como de factores de riesgo: la situación de pobreza, el sexo femenino y el hecho de haber tenido problemas de salud durante el desastre 36 . Profundizando la discusión en las variables cercanas al plano social y económico, los hallazgos del presente estudio son consistentes con lo observado en el trabajo conducido por Tracy et al 37 , quien estudió a la población del estado de Texas (Estados Unidos), a posteriori del huracán Ike que afectó la costa Texana en el año 2008.…”
Section: Aspectos éTicosunclassified